2023
DOI: 10.1097/olq.0000000000001769
|View full text |Cite
|
Sign up to set email alerts
|

Predominance of High-Level Tetracycline-Resistant Neisseria gonorrhoeae in Kenya: Implications for Global Implementation of Doxycycline Postexposure Prophylaxis for Prevention of Sexually Transmitted Infections

Abstract: Most archived Neisseria gonorrhoeae samples collected from 2008 to 2012 from Kenyan women had tet(M)-encoding high-level tetracycline resistance; this could reduce the efficacy of doxycycline postexposure prophylaxis against N. gonorrhoeae.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…The prevalence of the tetM gene in certain populations is significant, as observed by a study involving 50 endocervical swab specimen's positive for N. gonorrhoeae from women in Kenya. In this study, the American-type plasmid-mediated tetM gene was identified in 96% of the samples, suggesting that DoxyPEP for STI prevention might have limited efficacy against gonorrhea in sub-Saharan Africa 42 .…”
Section: Antimicrobial Resistance and Microbiome Disruptionmentioning
confidence: 76%
“…The prevalence of the tetM gene in certain populations is significant, as observed by a study involving 50 endocervical swab specimen's positive for N. gonorrhoeae from women in Kenya. In this study, the American-type plasmid-mediated tetM gene was identified in 96% of the samples, suggesting that DoxyPEP for STI prevention might have limited efficacy against gonorrhea in sub-Saharan Africa 42 .…”
Section: Antimicrobial Resistance and Microbiome Disruptionmentioning
confidence: 76%
“…We emphasize that the long-term impacts of doxyPEP on the N. gonorrhoeae population in the United States are unknown, as lineages may acquire new resistance alleles and introduction of lineages from other geographic regions is possible. 11,12 For example, a recent study found that strains encoding tetM are highly prevalent among women in Kenya, 13 and phylogenetic analysis of our global dataset identified several lineages with high-level tetracycline resistance not represented among GISP isolates (Supplementary Figure 2).…”
mentioning
confidence: 89%
“…Its efficacy can be attributed to its broad-spectrum activity and its proficient tissue penetration. 136,137 Macrolides: Azithromycin, a macrolide antibiotic, is commonly administered as a single-dose regimen for the treatment of Chlamydia trachomatis and Mycoplasma genitalium infections. Owing to its extended half-life and pronounced anti-inflammatory characteristics, it stands as a preferred choice for managing these infections.…”
Section: Antibiotics In the Treatment Of Reproductive Tract Infectionsmentioning
confidence: 99%